2016
DOI: 10.1038/cddis.2016.205
|View full text |Cite
|
Sign up to set email alerts
|

Activated c-Kit receptor in the heart promotes cardiac repair and regeneration after injury

Abstract: The role of endogenous c-Kit receptor activation on cardiac cell homeostasis and repair remains largely unexplored. Transgenic mice carrying an activating point mutation (TgD814Y) in the kinase domain of the c-Kit gene were generated. c-KitTgD814Y receptor was expressed in the heart during embryonic development and postnatal life, in a similar timing and expression pattern to that of the endogenous gene, but not in the hematopoietic compartment allowing the study of a cardiac-specific phenotype. c-KitTgD814Y m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 52 publications
2
42
0
Order By: Relevance
“…The ratio of these proteins to β-actin expression in experimental groups was shown and described in a, b, c sections endothelial regeneration, proliferation and differentiation of the heart cells. The binding of G-CSF to its receptors (G-CSFR) activates the JAK/STAT signaling pathways, Akt and BCL2 and inhibits BAX and caspase-3, and affects the BAX/BCL2 ratio (cell death index), and protects from myocytes by reducing and inhibiting apoptosis [41]. It was reported that the AMI-induced scar tissue area after G-CSF therapy was significantly reduced [42].…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of these proteins to β-actin expression in experimental groups was shown and described in a, b, c sections endothelial regeneration, proliferation and differentiation of the heart cells. The binding of G-CSF to its receptors (G-CSFR) activates the JAK/STAT signaling pathways, Akt and BCL2 and inhibits BAX and caspase-3, and affects the BAX/BCL2 ratio (cell death index), and protects from myocytes by reducing and inhibiting apoptosis [41]. It was reported that the AMI-induced scar tissue area after G-CSF therapy was significantly reduced [42].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, questions remain about their physiological role and relevance in adult hearts. Recently, Di Siena et al (2016) showed that constitutive activation of c-Kit receptor is associated with an increased cardiac myogenic and vasculogenic reparative potential after injury These results point towards a significant role of endogenous c-Kit + eCPCs in cardiac repair, homeostasis and survival.…”
Section: Potential Significancementioning
confidence: 99%
“…The differences of induction levels between Kit and EGFP in the overexpression experiments might reflect either post‐transcriptional regulation mechanisms or the involvement of additional DNA‐binding sites present in the Kit locus not included in the p18 and p70 constructs. The latter hypothesis is supported by the evidence that regulatory regions that promote Kit expression in PGCs and in other stem cell types are spread over 200 kb upstream to Kit ORF , indicating a complex level of regulation of Kit transcription. In agreement with our results, ChIP seq data showing Sox2 occupancy has been reported in close association to Oct4, Nanog, and Tcf3 within ±8 kb from the TSS of the Kit locus , suggesting a possible involvement of a pluripotency circuitry in the regulation of this gene.…”
Section: Discussionmentioning
confidence: 86%
“…Generation of Kit‐KO, Kit‐EGFP, and Sox2 loxP/loxP mice have been previously described . Sox2 loxP/loxP were intercrossed with Rosa26Cre‐Ert2 mice (Jackson Laboratories, Ann Harbor, MI) to generate Sox2 loxP/loxP , Rosa26Cre‐Ert2 mice.…”
Section: Methodsmentioning
confidence: 99%